2002
DOI: 10.1029/2000jd000215
|View full text |Cite
|
Sign up to set email alerts
|

Cloud susceptibility and the first aerosol indirect forcing: Sensitivity to black carbon and aerosol concentrations

Abstract: [1] Present-day global anthropogenic emissions contribute more than half of the mass in submicron particles primarily due to sulfate and carbonaceous aerosol components derived from fossil fuel combustion and biomass burning. These anthropogenic aerosols increase cloud drop number concentration and cloud albedo. Here, we use an improved version of the fully coupled climate/chemistry models to investigate cloud susceptibility and the first indirect effect of anthropogenic aerosols (the Twomey effect). We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
4
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(168 citation statements)
references
References 69 publications
9
152
4
3
Order By: Relevance
“…However, Bowman and Henze (2012) showed that for the short-lived greenhouse gas, O 3 , tropical emissions lead to an enhanced RF relative to extratropical emissions. This is also potentially important for aerosols, including direct effects, due to latitudinal changes in solar insolation, and indirect effects, due to regional differences in cloud regimes (Chuang et al, 2002). show that ascribing RF from short-lived forcing agents to individual locations based on proportional emissions is reasonable for comparing the climate impacts of developed countries, as a group, to developing countries.…”
Section: Ascribing Rf To the Gridmentioning
confidence: 99%
“…However, Bowman and Henze (2012) showed that for the short-lived greenhouse gas, O 3 , tropical emissions lead to an enhanced RF relative to extratropical emissions. This is also potentially important for aerosols, including direct effects, due to latitudinal changes in solar insolation, and indirect effects, due to regional differences in cloud regimes (Chuang et al, 2002). show that ascribing RF from short-lived forcing agents to individual locations based on proportional emissions is reasonable for comparing the climate impacts of developed countries, as a group, to developing countries.…”
Section: Ascribing Rf To the Gridmentioning
confidence: 99%
“…This suggests a globally important role for short-range transport of smoke from tropical fires on the easterly trade winds to nearcoast marine stratocumulus cloud decks. Chuang et al (2002) note that these clouds are particularly susceptible to changes in optical thickness from an influx of high aerosol number concentration because of the low marine aerosol number concentrations. In our simulations, fire aerosols cause a two-fold increase in cloud droplet number concentration (CDNC) in the low clouds in areas off the west coasts of South America and central Africa, as well as a 10 % decrease in cloud droplet effective radius in the same areas.…”
Section: Aerosol Direct Effectmentioning
confidence: 99%
“…Some studies have estimated a global cloud albedo forcing of −0.5 W m −2 and predict net positive forcing (Hansen et al, 2005(Hansen et al, , 2007, while others suggest a large cloud albedo forcing of between −0.9 W m −2 (Lohmann et al, 2000) and −1.68 W m −2 (Chuang et al, 2002) potentially Published by Copernicus Publications on behalf of the European Geosciences Union. 9068 D. V. Spracklen et al: Global cloud condensation nuclei sufficient to produce a net negative forcing due to carbonaceous combustion aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…However, carbonaceous combustion aerosol also contains particulate organic matter (POM), which can have a cooling effect on climate because it scatters solar radiation and can enable carbonaceous combustion aerosol to act as cloud condensation nuclei (CCN) and form cloud drops, increasing cloud albedo (Chuang et al, 2002;Lohmann et al, 2000) -the so-called first aerosol indirect effect (AIE). Some studies have estimated a global cloud albedo forcing of −0.5 W m −2 and predict net positive forcing (Hansen et al, 2005(Hansen et al, , 2007, while others suggest a large cloud albedo forcing of between −0.9 W m −2 (Lohmann et al, 2000) and −1.68 W m −2 (Chuang et al, 2002) potentially Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%